Teaching Simple Present Tense Using EGRA Technique - Nussy, Wenssy Steva; Oraile, Orpa Penina; Tiven, Punggulina Andawaty; Djirlay, Merlin; Kaidel, Devita; Ratmala, Dessy (Civiliza Publishing, 2024)
As one of Indonesia's underdeveloped, frontier, and outermost regions, Aru Regency faces significant challenges in providing quality English education, primarily due to a shortage of qualified English teachers. This shortage has resulted in students having limited exposure to the English language, particularly in foundational aspects such as grammar. Recognizing this issue, the community development team initiated a program aimed at improving students’ grammar proficiency, with a specific focus on the simple present tense. To achieve this, the team implemented the EGRA (Experience, Generalization, Reinforcement, Application) technique, a structured approach designed to enhance both understanding and application of grammar in a systematic manner. The community development program was conducted at SMP Jeljakaka, involving a class of 30 students. At the outset, a pre-test was administered to assess the students' baseline understanding of grammar. The results revealed that the majority of students had not yet mastered fundamental grammatical structures, particularly the simple present tense. Following the intervention using the EGRA technique, the students were given a post-test to measure their progress. The results indicated a significant improvement in their understanding and application of the simple present tense. This demonstrated the effectiveness of the EGRA technique in addressing gaps in grammar mastery while also highlighting the importance of structured and interactive teaching methods in enhancing students' language skills in challenging educational contexts.